Rural Women: A Thematic Perspective on Midlife - England, Joan; Finch, Jessie (Canadian Journal of Counselling and Psychotherapy, 2011)
A qualitative study was designed to hear the voices of rural women in South Dakota reflecting on their midlife experiences. Emerging themes constant with established theory included the importance of affiliation, religion, feelings of mastery, and interdependent relationships. Themes that differed included a broader definition of mastery as involving the well-being of their families along with personal accomplishments outside the family. These women viewed the reassessing of their dreams and goals as a continuing process in their lives rather than a separate thrust at midlife. All of these women reflected an attitude toward coping with life events rather than being captured by them.